THE NOTION OF ASPECT AND ITS SYSTEMATIC REPRESENTATION IN LINGUISTICS - Jurabayeva Dilnoza Zafarbek qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  article  investigates  the  linguistic  category  of  aspect  and  its systematic representation in English and Uzbek. Aspect is treated as a grammatical and semantic category that expresses the internal temporal structure of an event, including its duration, completion, repetition, and relation to the moment of speech or another reference point. The study is based on a comparative analysis of theoretical works on aspectology and descriptive grammars of English and Uzbek. The results show that English has a relatively fixed grammatical opposition between simple, progressive, perfect,  and  perfect  progressive  forms,  whereas  Uzbek  represents  aspect  through a more complex interaction of tense markers, participial forms, auxiliary verbs, lexical semantics, and contextual interpretation. The comparison demonstrates that English aspect  is  primarily  expressed  through  analytic  verb  forms,  while  Uzbek  aspectual meanings  are  often  realized  by  agglutinative  morphology  and  auxiliary  verb constructions.  The  article  concludes  that  aspect  should  be  analyzed  as  a  system combining grammatical, lexical, and discourse-level meanings rather than as a purely morphological category.